1988
DOI: 10.1111/j.1471-0307.1988.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the relation between bacterial growth and storage temperature in pasteurized milks of varying hygienic quality

Abstract: The shelf‐life of pasteurized milk was mainly determined by the level of contamination with Gram‐negative psychrotrophic bacteria. The length of lag phase of the bacteria was also important, although the generation times of the naturally contaminating flora seemed to be of little relevance except for milks where the shelf‐life exceeded 10 days at 6°C. The effect of temperature on growth of the contaminants could be accurately determined by the ‘square root’ plot but the conceptual minimum temperature for growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Identification and estimation of the relative proportions of bacterial types present was carried out according to the method previously described by Griffiths & Phillips (1988).…”
Section: D E N T I F I C a T I O N Of B A C T E R I Amentioning
confidence: 90%
See 2 more Smart Citations
“…Identification and estimation of the relative proportions of bacterial types present was carried out according to the method previously described by Griffiths & Phillips (1988).…”
Section: D E N T I F I C a T I O N Of B A C T E R I Amentioning
confidence: 90%
“…The initial psychrotroph count was determined by a Most Probable Number technique (Oblinger & Koburger 1975) using 50, 10 and 1 ml volumes of the freshly pasteurized milks (Griffiths & Phillips 1988).…”
Section: Bacteriological E X a M I N A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation coefficients obtained indicated that their relationship was linear ðr 2 > 0:93Þ. An accurate estimation of the lag time is very important for two reasons, the first being the extension of shelf life of chilled foods (Griffiths & Philips, 1988), and second being its role in the mathematical modelling of growth data.…”
Section: Modelling the Growth Of Pseudomonas Fluorescens And Candida mentioning
confidence: 98%
“…Similarly, the effect of low temperature storage on pasteurized fluid milk has also been studied (Muir et al, 1987;Phillips and Griffiths, 1987;Griffiths and Phillips, 1988). Although there is a consensus that lower storage temperatures lead to slower and reduced bacterial growth over time, the fluid milk manufacturer can do very little to control this factor once the milk has left the processing facility.…”
Section: Short Communicationmentioning
confidence: 96%